Grado de competitividad de la Empresa Mathi Store en el Cantón Alfredo Baquerizo Moreno Jujan, en el año 2023. - Alcívar Llorela, Jumary Janeth (2025)
This study addresses the analysis of the degree of competitiveness of the company Mathi Store, located in the canton Alfredo Baquerizo Moreno, Jujan, during the year 2023. With three years of experience in the market and a varied product offering, it faces challenges such as intense competition, lack of differentiation in its value proposition, poor digital visibility, and deficiencies in customer service. These limitations affect its ability to retain customers and adapt to changing trends and demands in the local environment. Through customer surveys, a SWOT analysis, and marketing techniques, the company's main strengths, weaknesses, opportunities, and threats were identified. Among the strengths are its strategic location, the quality of its products, and competitive prices. However, weaknesses include a lack of digital promotion, insufficient staff training, and poorly developed loyalty programs. In addition, the lack of innovation represents a barrier to differentiation in a highly competitive market. The study recommends implementing specific strategies to improve competitiveness, such as developing a digital marketing strategy that increases visibility on social media and e-commerce. It also proposes training staff to improve customer service and the shopping experience. These actions seek to strengthen Mathi Store's position in the local market, increase customer loyalty and adapt to a changing environment. By implementing these strategies, the company will be able to consolidate its growth and achieve competitive and sustainable performance in the long term.